Adaptive output feedback stabilization for switched p-normal nonlinear systems with unknown homogeneous growth rate. (February 2021) - Shu, Feng; Zhai, Junyong
Abstract: This paper investigates the problem of adaptive output feedback control for switched p -normal nonlinear systems with unknown homogeneous growth rate. A novel adaptive output feedback control scheme is first presented with the help of a dynamic gain technique, which renders the switched nonlinear systems with lower-triangular unknown homogeneous growth rate globally asymptotically stable. Then, the proposed control scheme can be extended to deal with a class of switched nonlinear systems with upper-triangular unknown homogeneous growth rate. Finally, two numerical examples are provided to verify the effectiveness of the proposed scheme.